Integrasi Metode Hermeneutik dalam Tafsir Tarbawi: Tantangan dan Implikasi dalam Pendekatan Pedagogis al-Qur’an - Ulum, Bahrul; Asy'ari, Nur Hasan (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2024)
Tarbawi's interpretation has so far referred to interpretation of the Al-Quran applied with an educational or pedagogical approach. The pedagogical approach in this course makes the Al-Quran the main source of learning, based on verses about education. The interpretation method generally uses thematic interpretation. This article examines the hermeneutic method in understanding the verses of the Koran related to education. The research results show that the use of hermeneutics in Tafsir Tarbawi can be done as long as it pays attention to existing interpretations. The method is to combine it with Islamic exegetical methods such as tafsir bil-ma'tsur (tafsir based on verses of the Koran and hadith) or tafsir bil-ra'yi (tafsir based on rational judgment). However, if Hermenetics is completely separated from existing interpretations, there will be a risk of interpretations that are out of their original context. This is because the application of hermeneutics in tarbawi interpretation can produce a variety of interpretations that can obscure the desired pedagogical goals. Therefore, hermeneutics must be carried out carefully so as not to violate Islamic principles or values. Interpretations that produce meanings that conflict with Islamic teachings will conflict with the objectives of Tafsir Tarbawi